1994
DOI: 10.1007/bf01092410
|View full text |Cite
|
Sign up to set email alerts
|

Was there a ?medieval warm period?, and if so, where and when?

Abstract: Abstract. It has frequently been suggested that the period encompassing the ninth to the fourteenth centuries A.D. experienced a climate warmer than that prevailing around the turn of the twentieth century. This epoch has become known as the Medieval Warm Period, since it coincides with the Middle Ages in Europe.In this review a number of lines of evidence are considered, (including climatesensitive tree rings, documentary sources, and montane glaciers) in order to evaluate whether it is reasonable to conclude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
136
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(147 citation statements)
references
References 44 publications
8
136
0
3
Order By: Relevance
“…It also provides valuable analysis of past temperature estimates for a region in the Southern Hemisphere, given that many studies have been Northern Hemisphere focused (Lamb 1965;Grove 1988;Hughes and Diaz 1994;Crowley and Lowery 2000;Bradley et al 2003;Mann et al 2009;Frank et al 2010;Graham et al 2011). Future research will focus on consolidating Australasian paleoclimate data with other Southern Hemisphere regions to advance our understanding of global change over the past millennium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also provides valuable analysis of past temperature estimates for a region in the Southern Hemisphere, given that many studies have been Northern Hemisphere focused (Lamb 1965;Grove 1988;Hughes and Diaz 1994;Crowley and Lowery 2000;Bradley et al 2003;Mann et al 2009;Frank et al 2010;Graham et al 2011). Future research will focus on consolidating Australasian paleoclimate data with other Southern Hemisphere regions to advance our understanding of global change over the past millennium.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the magnitude and timing of temperature fluctuations in the Southern Hemisphere during the so-called Medieval Climate Anomaly (MCA) warm (900-1250) or Little Ice Age (LIA) cool (1400-1700) intervals described from Northern Hemisphere climate reconstructions (Hughes and Diaz 1994;D'Arrigo et al 2006a;Mann et al 2009;Diaz et al 2011;Graham et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the overall lack of agreement about the worldwide distribution, precise timing, amplitude or cause of these fluctuations underlines the need for additional regional records to reconstruct climate change (e.g. Hughes and Diaz, 1994;Crowley and Lowery, 2000;Broecker, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The last 4000 yr of this time interval are characterized by several climatic fluctuations, the best identified among them being the Late Bronze Age-Iron Age (LBA, 3600-2600 cal yr BP; van Geel et al, 1996), the Roman Humid Period (RHP, 2600-1600 cal yr BP; Issar, 2003), the Dark Ages (DA, 1600-1150 cal yr BP; Berglund, 2003), the Medieval Climate Anomaly (MCA, 1150-650 cal yr BP;Lamb, 1965;Hughes and Diaz, 1994) and the LIA (650-150 cal yr BP; Bradley and Jones, 1993). In this work we integrated data from two different marine records from the western Algerian-Balearic Basin.…”
Section: Introductionmentioning
confidence: 99%
“…His studies pre-dated modern quantitative paleoclimatology so the values of temperature change that he attributed to this period are essentially anecdotal, and based largely on his own estimates and personal perspective. In revisiting the concept of a MWE, Hughes and Diaz (1996) reviewed a wide range of paleoclimatic data, much of it reported since Lamb's classic work (Lamb 1965). They concluded that "it is impossible at present to conclude from the evidence gathered here that there is anything more significant than the fact that in some areas of the globe, for some part of the…”
mentioning
confidence: 99%